Spectrum of carcinoembryonic antigen immunoreactivity from isolated ductal hyperplasias to atypical hyperplasias associated with infiltrating ductal breast cancer - Schmitt, F. C.; Andrade, L. (British Med Journal Publ Group, 1995)
Aims - To study the immunohistochemical expression of carcinoembryonic antigen (CEA) in ductal hyperplasia of the breast and to investigate its putative relation with atypia and co-existing infiltrating ductal carcinoma.Methods - Paraffin wax embedded tissue from 37 cases of isolated ductal hyperplasia (five with atypia and 32 without atypia) and 25 cases of ductal hyperplasia associated infiltrating ductal carcinoma (IDC) (seven with atypia and 18 without atypia) was stained with a monoclonal anti-CEA antibody using a standard avidin biotin immunoperoxidase method.Results - CEA immunoreactivity was observed in eight (12.8%) ductal hyperplasia cases. The percentage of CEA positivity in ductal hyperplasia cases with atypia (33.3%) was substantially higher than that observed in cases of ductal hyperplasia without atypia (8.0%). Six cases of ductal hyperplasia associated IDC reacted with CEA; in these six cases the neoplastic cells of the co-existing carcinoma were also CEA positive. The percentage of CEA immunoreactivity in ductal hyperplasia associated IDC was higher than that observed in isolated ductal hyperplasia (24.0 v 5.4%). The percentage of CEA immunoreactivity in atypical ductal hyperplasia associated IDC was similar to that observed in IDC alone (42.9 v 40.0%).Conclusions-The presence of CEA immunoreactivity has been confirmed in benign proliferative breast lesions. The prevalence of such immunoreactivity increases from 3.1% in isolated, nonatypical ductal hyperplasia to 42.9% in atypical ductal hyperplasia associated IDC. This finding and the similarity of the frequency of CEA positivity in atypical ductal hyperplasia associated IDC and in IDC alone suggests that there is a pathogenetic link between ductal hyperplasia and some types of breast cancer.
Keywords: DUCTAL HYPERPLASIA; CARCINOEMBRYONIC ANTIGEN; BREAST CANCER